ANALISIS UNSUR KEBUDAYAAN ETNIS TIONGHOA PADA FILM CEK TOKO SEBELAH - Yu'thika Hasanah; Asaas Putra (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
This study aims to reveal the forms of Tionghoa society Elements in the “Cek Toko Sebelah” movie. The methods used in the process of description, reduction, and also for the films. Film is showing the lives of Tionghoa people who work as traders and have two sons. Based on the results of research and the search for meaning and form of society, can be certified “Cek Toko Sebelah” The Movie shows the universal elements of the Tionghoa tradition through the scene and use of the property in each scene. The forms of Tionghoa cultural elements are ideas, and concepts on the concept, he form of behavior and activity, and in the form of objects of human works in the form of productive tools, the use of cutlery, clothing, and art form of maneki neko.